GABA as a rising gliotransmitter - Yoon, Bo-Eun; Lee, C. Justin (Frontiers in Neural Circuits, 2014)
Gamma-amino butyric acid (GABA) is the major inhibitory neurotransmitter that is known to be synthesized and released from GABAergic neurons in the brain. However, recent studies have shown that not only neurons but also astrocytes contain a considerable amount of GABA that can be released and activate GABA receptors in neighboring neurons. These exciting new findings for glial GABA raise further interesting questions about the source of GABA, its mechanism of release and regulation and the functional role of glial GABA. In this review, we highlight recent studies that identify the presence and release of GABA in glial cells, we show several proposed potential pathways for accumulation and modulation of glial intracellular and extracellular GABA content, and finally we discuss functional roles for glial GABA in the brain.